How CCAFS works with women and female empowerment in Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
In this video, Caroline Odera, a consultant for the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East Africa and World Neighbors talks about her work with women and female empowerment in lower Nyando Kenya. She has noticed several changes in the community; women starting micro-businesses, earning an income and making enough money to send their children to secondary education something that wasn't happening before these targeted empowerment and capacity building activities. Learn more: www.ccafs.cgiar.org